Peningkatan Skill Pelaku Usaha Kopi di Sukoharjo dengan Pelatihan Uji Sensori dan Teknik Seduhan Kopi - Laela Nur Rokhmah (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2023)
Sensory Skill is a skill that must be owned by a barista or coffee brewer. Sensory Skills are skills for analyzing and characterizing coffee that involve the senses of taste, sight and smell. This skill is important because a barista is required to be able to brew and serve coffee with a distinctive taste and according to the wishes of the customer. Various characters and flavors of coffee that can be produced. The same coffee will produce different flavor characters with different brewing techniques. That is the uniqueness of coffee. So that the skill of brewing coffee is as important as the skill of testing the taste of coffee. In this activity, the 2 activities were combined in the form of a competition. So that the participants can immediately put into practice the exercises they have acquired. A total of 32 participants took part in the coffee brewing competition which is a form of practicing coffee brewing techniques. A total of 52 participants took part in the training activities. The brewing results were then tested and assessed based on preference involving 3 trainees and 2 trained panelists. As a result of this activity, the participants not only knew but also practiced coffee brewing techniques as well as coffee sensory skills. In addition, the 3 best participants in terms of brewing coffee were obtained.   ABSTRAK                 Skill Sensori merupakan salah satu skill yang harus dimiliki oleh seorang barista atau penyeduh kopi. Skill Sensori yaitu skill untuk menganalisis, mengkarakterisasi kopi yang melibatkan indra perasa, penglihatan dan penciuman. Skill tersebut penting karena seorang barista dituntut mampu untuk menyeduh dan menyajikan kopi dengan citarasa khas dan sesuai dengan keinginan customer. Beragam karakter dan citara kopi yang dapat dihasilkan. Satu kopi yang sama akan menghasilkan karakter citarasa berbeda dengan teknik seduhan yang berbeda. Itulah keunikan dari kopi. Sehingga skill menyeduh kopi sama pentingnya dengan skill menguji citarasa kopi. Pada kegiatan ini dikombinasikan 2 kegiatan tadi dalam bentuk lomba. Sehingga para peserta bisa langsung mempraktekkan latihan yang sudah diperolehnya. Sebanyak 32 peserta ikut dalam lomba menyeduh kopi yag merupakan bentuk dari praktek teknik menyeduh kopi. Total peserta yang mengikuti kegiatan pelatihan sebanyak 52 peserta. Hasil seduhan kemudian diuji dan dinilai berdasarkan kesukaan yang melibatkan 3 peserta pelatihan dan 2 orang panelis terlatih. Hasil kegiatan tersebut, peserta tidak hanya mengetahui sekaligus juga mempraktekkan teknik seduhan kopi juga skill sensori kopi. Selain itu, diperoleh 3 peserta terbaik dalam hal menyeduh kopi.